The Best Things Ever Said About Parenting - Bill Carmichael & Nancie Carmichael
Inspiring authors Bill and Nancie Carmichael have compiled a book of quotations to inform, challenge, encourage, and direct parents. The Carmichaels believe the home is a place of refuge, formation, boundaries, celebration, connection, legacy, and purpose. Each of these seven themes is introduced with over 200 quotations. This is an ideal book for parents who are working to build healthy families.